The results of external quality assessment programme on urine leukocyte and erythrocyte counting in Poland - Ćwiklińska, Agnieszka (Array, 2020)
Introduction: Urine particle analysis is an important diagnostic tool. The aim of this study was to evaluate the quality of urine leukocyte (WBC) and erythrocyte (RBC) counting results obtained with manual and automated methods in Polish laboratories participating in the international external quality assessment (EQA) programme. Materials and methods: 1400 WBC and RBC counting results were obtained from 183 laboratories in EQA surveys organised by Labquality (Helsinki, Finland) from 2017 to 2019. The between-laboratory coefficient of variation (CV), the percentage difference between the laboratories' results and target values (Q-score (%)), as well as modified Youden plots were analysed. Results: For automated method groups, the medians of inter-laboratory CVs varied from 14% to 33% for WBC counting and from 10% to 39% for RBC counting. For manual method groups, the medians of CV varied from 53% to 71% (WBC) and from 55% to 70% (RBC), and they were significantly higher, in comparison to CVs for most automated method groups (P <0.001). The highest percentage of results outside the target limits (36%) and the highest range of Q-score (%) (from - 93% to 706%) were observed for laboratories which participated in the surveys for the first or second time. The percentage of deviating results and the ranges of Q-score decreased with an increased frequency of laboratories’ participation in the surveys. Conclusions: The quality of manual methods of urine WBC and RBC counting is unsatisfactory. There is an urgent need to take actions to improve laboratories’ performance and to increase harmonisation of the results.